HUBUNGAN ANTARA INTENSITAS PUASA SUNNAH SENIN KAMIS DENGAN KECERDASAN EMOSIONAL SANTRI DI SMP PONDOK PESANTREN AR RISALAH LUBUKLINGGAU - Mega Agustinah; Muhammad Isnaini; Nurlaila Nurlaila (PAI RAFAH, 2020)
Rasulullah SAW most often performs one of the fasts on Monday and Thursday. Rasulullah did it with a state of a heart full of enthusiasm and earnest and manifested in the form of a deep appreciation of the meaning and meaning contained in fasting and actions as the intensity of the fast itself. Fasting can control emotions, strengthen awareness, and create emotional balance. This study aims to determine the intensity of the Sunnah fasting Monday Thursday for students at the Ar Risalah Lubuklinggau Islamic Boarding School Middle School, to determine the emotional intelligence of the students at the Ar Risalah Lubuklinggau Islamic Boarding School Middle School, and to determine the relationship between the intensity of Monday's fasting on the emotional intelligence of the students at the Ar Risalah Islamic Boarding School Junior High School. Lubuklinggau treatise. This research method uses a quantitative research approach. Based on the research approach, the type of research used is correlation research. The correlation technique used is the product-moment correlation technique. Which in this study is to determine whether there is a relationship between the intensity of the Sunnah fasting Monday Thursday with the emotional intelligence of students.The results of this study indicate: (1) The intensity of the Sunnah fasting Monday Thursday the students of the Ar Risalah Lubuklinggau Islamic boarding school have an average percentage of 67.5% which is classified as moderate. (2) The emotional intelligence of the Ar Risalah Lubuklinggau Islamic boarding school students has an average percentage of 70% which is classified as moderate. (3) There is a significant relationship between the intensity of the Sunnah fasting Monday Thursday with the emotional intelligence of the students of the Ar Risalah Lubuklinggau Islamic boarding school. Thursday with at-count value of 0.489 is greater than t-table with a significant level of 5%, namely 0.220 and a significant rate of 1%, namely 0.286 which indicates tcount> table with a comparison of 0.220 <0.489> 0.286